2002
DOI: 10.1074/jbc.m203254200
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae Acyl-CoA Oxidase Follows a Novel, Non-PTS1, Import Pathway into Peroxisomes That Is Dependent on Pex5p

Abstract: The peroxisomal protein acyl-CoA oxidase (Pox1p) of Saccharomyces cerevisiae lacks either of the two well characterized peroxisomal targeting sequences known as PTS1 and PTS2. Here we demonstrate that peroxisomal import of Pox1p is nevertheless dependent on binding to Pex5p, the PTS1 import receptor. The interaction between Pex5p and Pox1p, however, involves novel contact sites in both proteins. The interaction region in Pex5p is located in a defined area of the amino-terminal part of the protein outside of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
141
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(147 citation statements)
references
References 79 publications
4
141
0
2
Order By: Relevance
“…Recently, Distel and coworkers (Klein et al, 2002) indicated that S. cerevisiae acyl-CoA oxidase, a protein that lacks both a PTS1 and PTS2, interacts with the N-terminus of ScPex5p and Purdue and Lazarow (2001) reported that the region of ScPex5p responsible for this interaction was mapped to residues 136 -292 of ScPex5p, a domain clearly distinct from the TPR repeat region. Whether the corresponding region of HpPex5p is involved in AO binding is the topic of current investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Distel and coworkers (Klein et al, 2002) indicated that S. cerevisiae acyl-CoA oxidase, a protein that lacks both a PTS1 and PTS2, interacts with the N-terminus of ScPex5p and Purdue and Lazarow (2001) reported that the region of ScPex5p responsible for this interaction was mapped to residues 136 -292 of ScPex5p, a domain clearly distinct from the TPR repeat region. Whether the corresponding region of HpPex5p is involved in AO binding is the topic of current investigations.…”
Section: Discussionmentioning
confidence: 99%
“…This creates a window where they may be temporarily active in the cytosol. In some studies, 15 to 25% of the ␤-oxidation enzyme activities were found in the cytosol of yeast (6,10,14,26). This explains why wild-type yeast can synthesize PHA in the cytosol and why PHA synthesized in wild-type yeast and the pex5 mutants contains PHA monomers with C backbones different in length than the fed fatty acids.…”
Section: Discussionmentioning
confidence: 93%
“…The acyl coenzyme A (acyl-CoA) oxidase Fox1p follows a novel, non-PTS1, import pathway that is also dependent on Pex5p (14). In pex5 mutants, both Fox2p and Fox1p are found in the cytosol but Fox3p is located in peroxisomes (25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pex7p functions in cargo binding, whereas the coreceptors are required for membrane docking and recycling. Evidence exists for a third pathway that is independent of a PTS1, but requires the N‐terminal domain of Pex5p 16, 17. Sometimes referred to as the PTS3 pathway, to date no PTS3 consensus sequence has been described 18.…”
mentioning
confidence: 99%